Exploring Pruritus in Bullous Pemphigoid: Analysis of QOL Metrics and Potential Biological Mechanisms - Olive C. Osuoji; Taryn DeGrazia; Robin Rolader; Emily F. Cole; Katy Lawson; Henry Hilley; Yanyan Xing; Liang Han; Sarah Chisolm; Henry Claussen; Xiaobo Yan; Yuxian Sun; et al. (JID Innovations)
Bullous pemphigoid is a devastating autoimmune blistering disease with need for improved therapeutics. Limited data are available on the overall burden of pruritus and alterations over time; however, treatment of itch-specific pathways may provide novel therapeutics. In this paper, we analyzed the QOL impact particularly related to itch and determined corresponding changes in intraepidermal nerve fiber density and gene expression. A total of 43 patients with bullous pemphigoid were followed prospectively on standard-of-care treatment and showed average Bullous Pemphigoid Disease Area Index total activity score decrease from 19.1 ± 19.2 to 8.2 ± 11.3 and improvement in QOL measures Autoimmune Bullous Disease Quality of Life, Treatment of Autoimmune Bullous Disease Quality of Life, and ItchyQoL. At baseline, intraepidermal nerve fiber density in patients with bullous pemphigoid and atopic dermatitis were significantly lower than in healthy controls (7.3 ± 1.5 and 3.2 ± 2.0 vs 9.7 ± 5.4 fibers/mm, P = .031) and increased from baseline to follow-up visit (11.7 ± 0.4 and 5.8 ± 2.7), although only atopic dermatitis reached statistical significance (P = .018). S100A8, S100A9, CCL17, and CCL18 genes were highly upregulated in the skin of patients with bullous pemphigoid compared with those in healthy controls. Our data provide evidence for improvements in itch-related QOL over time on standard-of-care therapies with unique alterations in inflammatory mediators related to early immune cell activation and recruitment.